2017
DOI: 10.1080/14397595.2017.1349573
|View full text |Cite
|
Sign up to set email alerts
|

Post-marketing surveillance study of the long-term use of mizoribine for the treatment of lupus nephritis: 2-Year results

Abstract: Objectives: To understand the status of mizoribine use in patients with lupus nephritis (LN) and to collect safety-and efficacy-related data on 2-year treatment with mizoribine. Methods: A continuous survey was conducted between March 2010 and July 2015.Results: The analysis set included 559 patients (mean age 39.5 years, females 82.6%, mean duration of systemic lupus erythematosus (SLE) 8.4 years, mean duration of LN 5.9 years). Renal function was satisfactory for 6 months, but worsened from 12 months, with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The combination of MZR and CNI was enrolled as part of the same group as the combination of MMF and CNI in the present study, because it is a commonly used multi-targeted therapy for lupus nephritis in Japan [ 10 , 11 ]. Seroconversion rate and antibody titres were 75% and 473.5 U/ml (IQR, 233–1524.5) in patients with MZR and CNI ( n = 4), and 53.3% and 2.67 U/ml (IQR, 0–16.8) in those with MMF and CNI ( n = 15), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of MZR and CNI was enrolled as part of the same group as the combination of MMF and CNI in the present study, because it is a commonly used multi-targeted therapy for lupus nephritis in Japan [ 10 , 11 ]. Seroconversion rate and antibody titres were 75% and 473.5 U/ml (IQR, 233–1524.5) in patients with MZR and CNI ( n = 4), and 53.3% and 2.67 U/ml (IQR, 0–16.8) in those with MMF and CNI ( n = 15), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 63.3% of patients achieved complete or partial remission, and only 3.6% of patients experienced serious adverse drug reactions within 2 years of mizoribine treatment, and the authors concluded that mizoribine was safe and effective (Figure 93). 800 Practice Point 10.2.3.2.5: The total duration of initial immunosuppression plus combination maintenance immunosuppression for proliferative LN should not be <36 months.…”
Section: Rationalementioning
confidence: 99%
“…146,147 A post-marketing surveillance study that included 559 patients on mizoribin plus steroids (with or without tacrolimus) showed renal remission in 63.3% of patients, with 26.5% achieving complete renal remission at week 24, and a good safety profile. 148 More studies are needed in order to establish mizoribin efficacy versus placebo or other drugs in LN patients.…”
Section: Other Immunosuppressantsmentioning
confidence: 99%